Trapped cystofix: Laparoscopic modality to untie - Assikin Muhamad; Syamim Johan; Allim Khairuddin; Firdaus Hayati; Alvin Oliver Payus; Zainal Adwin Zainal Abidin d (Elsevier Inc., 2021)
Suprapubic catheterization (SPC) is a temporary measure to relieve acute urinary retention (AUR). Despite being effective, it can lead to complications such as colon perforation, haematuria, and bladder wall spasm. We present a 52-year-old lady with cystofix for underlying urethral stricture presented with AUR. A new SPC was inserted to drain the urine. However, the SPC had looped and entangled with her cystofix, and laparoscopic removal of cystofix and insertion of a new SPC was done. In conclusion, trapped cystofix to the SPC tube is a potential complication during SPC insertion that can be avoided with appropriate care.